Flash flood simulation based on distributed hydrological model in future scenarios - Liu, Qi; Zhang, Nan; Wang, Lingling; Yu, Kunxia; Wu, Jiayi; Wang, Jingqi; Ma, Meihong (Frontiers in Earth Science, 2025)
Extreme rainfall events are frequent, particularly in economically underdeveloped hilly areas, where conventional hydrological models struggle to accurately simulate the formation of flash floods. Therefore, this study focuses on the Daxi River Basin in Guangdong Province. First, CMIP6 precipitation data is utilized to analyze the future precipitation variations on interannual and monthly scales. Compared to the baseline period, the annual precipitation increases under all three scenarios. Next, design storms with a return period greater than 2 years are allocated into rainfall patterns. By combining the accumulated precipitation with the soil moisture content, different distributed hydrological models are applied to calculate the corresponding flood discharges for different rainfall events. The results indicate that: 1) Precipitation under the SSP5-8.5 scenario is generally higher than under the SSP1-2.6 and SSP2-4.5 scenarios, with the SSP1-2.6 scenario showing the mildest increase. 2) The peak flood simulated by the CREST model are relatively low, at 235.4 m³/s, with fewer precipitation events covered, which is significantly lower than the simulation accuracy of the CNFF model. 3) The Daxi River Basin has a low probability of experiencing flash flood disasters exceeding the 10-year return period in the period from 2026 to 2070. The above research results will provide important references for flash flood disaster prevention in similar basins.